Modification of immunosuppressive agents in a kidney transplant recipient with COVID-19 and acute kidney injury - Thanawat Vongchaiudomchoke; Vittawin Sawangduan; Tosapon Sinpanee; Nipon Chalermphunchai; Kumtorn Lelamali; Kajohnsak Noppakun (Journal of Infection in Developing Countries)
Introduction: An outbreak of coronavirus disease-19 (COVID-19) has occurred in different parts of the world. Although a large piece of information regarding the epidemiology, clinical features, and management of COVID-19 has been reported in the general population, there is very limited data regarding organ transplant recipients, particularly regarding the management of maintenance immunosuppressive agents during infection.